2016
DOI: 10.1016/j.jtcvs.2016.04.093
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of surgical repair of pediatric coronary artery fistulas

Abstract: Surgical repair of isolated congenital coronary artery fistula in pediatric patients can be performed with low mortality and morbidity. Careful evaluation after surgery is necessary to monitor the occurrence of residual shunt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…Although the results are variable, residual leakage from or recanalization of the CAF has been found in 10% of transcatheter or surgical management cases (70,71). Zhang et al (72) reported that CAF recanalization occurs within the 1st year, suggesting the importance of evaluating for residual shunt during the early postoperative period. Despite the fact that a residual shunt smaller than 2-3 mm could be observed without further intervention, close monitoring should be performed during the postprocedural follow-up period (68,72).…”
Section: Postprocedural Complicationsmentioning
confidence: 99%
“…Although the results are variable, residual leakage from or recanalization of the CAF has been found in 10% of transcatheter or surgical management cases (70,71). Zhang et al (72) reported that CAF recanalization occurs within the 1st year, suggesting the importance of evaluating for residual shunt during the early postoperative period. Despite the fact that a residual shunt smaller than 2-3 mm could be observed without further intervention, close monitoring should be performed during the postprocedural follow-up period (68,72).…”
Section: Postprocedural Complicationsmentioning
confidence: 99%
“…Successful SL of the fistula and reconstruction of the CS was performed in an adult male with a congenital RCA-CS fistula, which was associated with aneurysmal dilatation of the CS and stenosis of the CS ostium[ 3 ]. In the patient series reported by Zhang et al[ 52 ], SL of isolated congenital CAFs was related to lower morbidity and mortality associated with residual shunt in 8/47 (17%) patients, two of whom required PTE. Based on the findings of adenosine 13 N-ammonia PET-CT in our five patients, transcutaneous or surgical intervention was avoided in four subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In cases with a very short and unrestricted fistulous route, for example, a left coronary-to-left heart chamber fistula without an ideal landing zone, TCC may lead to a high risk of device embolization and therefore, should be attempted with caution in these patients. 5,7,10,15,16) Surgical closure should still be employed in these clinical scenarios: CCFs accom-panied by a large saccular coronary artery aneurysm formation, especially in the case of an aneurysm compressing the adjacent structures, necessitating concomitant arterioplasty and aneurysmectomy; a large and wide CCF without a narrow part to safely anchor the occluder device; extreme vessel tortuosity that causes the inability to deliver a catheter far enough distally; the presence of diffuse or multiple drainage sites and difficulty in achieving complete occlusion; the presence of normal coronary branches too close to the drainage site to allow optimal device positioning; patients with significant coronary artery stenotic lesions who need concomitant coronary artery bypass surgery or need concomitant surgery for other cardiac malformations; or young patients with body weight less than 5 kg (the catheter size is not sufficiently small to be introduced into small coronary arteries). 7,10,[15][16][17] Procedural technical aspects: TCC of large CCFs remains one of the most complicated interventional procedures.…”
Section: Discussionmentioning
confidence: 99%